Analisis Kerusakan Pada Crane Kapal Km. Sabuk Nusantara 110 - Eka Nurmala; T. M. Jamil; Sulastriani R.; Baihaqi Baihaqi; Sabaruddin Sabaruddin; Rahmat Kurnia; Indra Dwi Kurniawan (Journal on Education, 2025)
Ships are a means of transportation for transporting people or goods that move in waters that have the best local routes between islands or internationally between countries. Ships have a vital role in the smooth running of the world economy, which functions to distribute goods using waterways for developed and developing countries. This study uses a qualitative method that is presented in descriptive analysis. The results of this study are: 1) Hydraulic oil must be controlled frequently every week; 2) Before turning on the crane, the crane should be pumped first; 3) Give a break for the crane; 4) Always check the hydraulic oil regularly; 5) Well-scheduled maintenance; and 6) Well-planned preventive maintenance.